2012
DOI: 10.1016/j.cell.2012.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Mono-Uridylation of Pre-MicroRNA as a Key Step in the Biogenesis of Group II let-7 MicroRNAs

Abstract: RNase III Drosha initiates microRNA (miRNA) maturation by cleaving a primary miRNA transcript and releasing a pre-miRNA with a 2 nt 3' overhang. Dicer recognizes the 2 nt 3' overhang structure to selectively process pre-miRNAs. Here, we find that, unlike prototypic pre-miRNAs (group I), group II pre-miRNAs acquire a shorter (1 nt) 3' overhang from Drosha processing and therefore require a 3'-end mono-uridylation for Dicer processing. The majority of let-7 and miR-105 belong to group II. We identify TUT7/ZCCHC6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
349
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(364 citation statements)
references
References 73 publications
13
349
1
1
Order By: Relevance
“…On the other hand, additional processing steps or a modified biogenesis pathway is used for other noncanonical miRNAs (groups 2 through 6). The production of group 2 miRNAs requires monouridylation of premiRNAs for their efficient processing by DICER, because these pre-miRNAs have a short (1 nt) 3′ overhang (39). Most vertebrate let-7 members and miR-105 belong to group 2.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, additional processing steps or a modified biogenesis pathway is used for other noncanonical miRNAs (groups 2 through 6). The production of group 2 miRNAs requires monouridylation of premiRNAs for their efficient processing by DICER, because these pre-miRNAs have a short (1 nt) 3′ overhang (39). Most vertebrate let-7 members and miR-105 belong to group 2.…”
Section: Discussionmentioning
confidence: 99%
“…99 Sequencing data revealed that the loop of pre-miRNA let-7 has a tetra-nucleotide sequence required for Lin28 binding and consequently Lin28/TUT4 uridylation. 109 Furthermore, knockdown of TUT4 and Lin28 in cancer cells decreased the level of stem cell markers, suggesting that they are required for the maintenance of a tumoral stem cell phenotype (Fig. 3).…”
mentioning
confidence: 99%
“…This modification impairs the stability of prelet-7, resulting in reduced levels of let-7. In addition, monouridylation has been shown to be required for the processing of some miRNA precursors (12). Deep sequencing analysis reveals that precursor uridylation is a widespread phenomenon occurring in many miRNA families in animals (13).…”
mentioning
confidence: 99%